Pengaruh Kinerja Keuangan Daerah terhadap Pertumbuhan Ekonomi di Provinsi Jambi Tahun 2019-2023 - Nhada Patricia Manullang; Siti Hodijah; Rosmeli Rosmeli (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the development of regional financial performance and its effect on economic growth in Jambi Province during the 2019–2023 period. Regional financial performance is measured using the Regional Financial Independence Ratio and the Fiscal Decentralization Degree (FDD), while economic growth is proxied by Gross Regional Domestic Product (GRDP). This research employs a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS), the Directorate General of Fiscal Balance (DJPK), and regional government financial reports covering 11 regencies/cities in Jambi Province. The analytical method applied is panel data regression using the Random Effect Model (REM). The results indicate that both regional financial performance and economic growth in Jambi Province experienced fluctuations throughout the study period. Partially, the Fiscal Decentralization Degree (FDD) has a positive and significant effect on GRDP, with a probability value of 0.0138. In contrast, the Regional Financial Independence Ratio does not have a significant effect on GRDP, as indicated by a probability value of 0.8843. Simultaneously, FDD and the Regional Financial Independence Ratio significantly affect GRDP, with an F-statistic probability value of 0.0390. The coefficient of determination (R²) is 0.1173, indicating that 11.73% of GRDP variation can be explained by the two variables, while the remaining 88.27% is influenced by other factors outside the research model. This study concludes that strengthening regional fiscal capacity through the optimization of local own-source revenue and fiscal decentralization policies is essential for promoting sustainable economic growth in Jambi Province.